PENGARUH KOMITMEN PROFESIONALTERHADAP TEKANAN ANGGARAN WAKTUYANG DIRASAKAN DAN PERILAKUDISFUNGSIONAL AUDIT - Wahyuni, Sri (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
This study aimed to determine the effect of professional commitment on perceivedtime budget pressure and underreporting of time behavior. This study conductedwith survey method on auditors working in second tier audit firms in Indonesia. Unitanalyses are individual auditors at all positions: junior, senior, manager/supervisor,and partner. Research samples are 70 respondents. This research uses pathanalysis as data analysis. This result of this research showed that professionalcommitment affective and professional commitment normative has positive andsignificant influence to perceived time budget pressure but not significant influenceto underreporting of time behavior, while the professional commitment continuancenot significant influence to perceived time budget pressure but has negative andsignificant influence to underreporting of time behavior. Perceived time budgetpressure has positive and significant influence to underreporting of time behavior.Perceived time budget pressure mediate professional commitment affective andprofessional commitment normative to underreporting of time behavior, while theperceived time budget pressure is not mediate professional commitmentcontinuance to underreporting of time behavior.Keywords: Professional commitment, perceived time budget pressure,underreportingof time behavior